أثر الاستثمار الأجنبي المباشر في نقل التكنولوجيا إلى الدول النامية حالة الصين - بوظراف، الجيلالي (جامعة أحمد دراية أدرار, 2011)
Through This article, we propose to undertake a study on the relationship between technology transfer through foreign direct investment and the factors of local production. This operation requires a prior existence of some market conditions However, FDI is attracted by countries with a return of high capacity, a workforce that qualify an innovation system developed. Indeed, technology and productivity of domestic firms can improve if foreign firms entering the local market by new technologies, however, they provide technical assistance and also when they commit to train professionals for local firms the implementation of programs and retraining.
سندرس في هذا المقال الرابطة بين نقل التكنولوجيا من خلال الاستثمار الأجنبي المباشر وعوامل الإنتاج الدولية وعوامل الإنتاج المحلية. إن عملية النقل هذه تتطلب أولويات في السوق المحلي، فالمعاينات والتقارير الدولية أبرزت بأن الاستثمار الأجنبي المباشر ينجذب نحو الدول المالكة لمردودية عالية ويد عاملة مؤهلة ونظام تجديد متطور. إذ باختراق الشركات الأجنبية للسوق المحلية تتحسن التكنولوجيا والإنتاجية محليا نتيجة للتقنية الجديدة ويتوافق هذا مع العمل على الضمان الكافي للمساعدة التقنية والتكوين الجيد لإطارات الشركات المحلية عن طريق وضع برامج التكوين والتدريب المهني الدائمين.
Keywords: الدول النامية -- الصين -- الاستثمار الأجنبي المباشر -- نقل التكنولوجيا -- النمو الاقتصادي